CLEANED: un outil rapide d’évaluation ex-ante des impacts environnementaux, climatiques et économiques de systèmes de production animale - Example du Sénégal - Hoek, Rein van der (2023)
This presentation was part of a short training on the CLEANED environmental assessment tool for agricultural experts in Senegal. The training included a case study on the Ferlo region of Senegal where cow milk production by women farmers is well established. Dry season feed availability is however a main constraint and there is therefore a need to develop a semi-intensive system with improved feed and forage options. Based on farm visits and discussions with women farmers and experts, the productive, environmental and economic performance of a typical farm was assessed using the CLEANED tool. This provided valuable insights into the current situation and directions for possible intervention strategies.